Efek Paparan Asap Pengolahan Ikan dengan Cara di Panggang terhadap Indeks Trombosit pada Pedagang Makanan di Kota Palangka Raya - Dwi Purbayanti; Syahrida Dian Ardhany (Borneo Journal of Medical Laboratory Technology, 2018)
Fish processing by grilled can produce emissions that contribute to pollutants in the air, which contain toxic chemical compounds that can provide short-term and long-term effects on human health. Some studies report a positive relationship between the amount of exposure to air pollution and the platelet index. The research was conducted on the subject of grilled fish sellers in Palangka Raya (73 respondents) and the control was fish food seller without selling grilled fish (33 respondents). Measurement of platelet indices (MPV, PDW, P-LCR, and PCT) used KX300 Hematology Analyzers. The results showed a significant difference in platelet indices for MPV, PDW and P-LCR parameters in the exposed group compared to controls, with values in the exposed group higher than controls and for PCT parameters, there was no significant difference even though the exposure value was higher than the control. The content of harmful chemical compounds present in the smoke of processing grilled fish can increase platelet activation that can lead to inflammation.